Temperature-dependent development and reproduction of the cowpea weevil, Callosobruchus maculatus F., in mungbean: Estimating a target temperature for its control using aeration cooling. (May 2021) - Daglish, Gregory J.; Jagadeesan, Rajeswaran; Nayak, Manoj K.
Abstract: The bruchid, Callosobruchus maculatus F., commonly known as the cowpea weevil, infests stored mungbean and other legumes. Aeration cooling has potential as a non-chemical means of managing this species in stored legumes. Population growth of C. maculatus in mungbean was investigated at nine constant temperatures (15, 17.5, 20, 22.5, 25, 27.5, 30, 32.5 and 35 °C) at 60% RH so that a target temperature for cooling could be estimated. We used two laboratory strains: Strain 1 and Strain 2 that had been in culture for 16–17 years and 1–2 years respectively. The results for the two strains were very similar. Egg to adult development occurred between 20 and 35 °C for Strain 1 and 17.5 and 35 °C for Strain 2. The optimal temperature for population growth was estimated to be 32.2 and 33.7 °C for Strains 1 and 2, respectively. The estimated lower threshold for population growth, i.e. the temperature at which population growth is zero, was 17.5 °C for Strain 1 compared with 17.1 °C for Strain 2. Based on our results, we recommend a target temperature of 17 °C for aeration cooling to manage C. maculatus infestations in mungbean during storage. Highlights: Population growth of Callosobruchus maculatus in mungbean impacted by temperature. Estimated optimal temperature for population growth was 32.2–33.7 °C. Estimated threshold temperature for population growth was 17.1–17.5 °C. Aeration cooling target of 17 °C is recommended to manage this pest in mungbean.